Interest rate modelling in the multi-curve framework : foundations, evolution and implementation - Henrard, Marc; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Following the financial crisis dramatic market changes, a new standard in interest rate modelling emerged, called the multi-curve framework. The author provides a detailed analysis of the framework, through its foundations, evolution and implementation. The book also covers recent extensions to collateral and stochastic spreads modelling.
Keywords: Science